Tourist Service - Guerrero Vanegas, Joaquin
This work is about what an entrepreneur is, the development of our tourist service and the strategies to be a successful entrepreneur developing our tourist service. Knowing what an entrepreneur is crucial if you want to be one. In the work, you can notice that an entrepreneur is someone who starts a business by himself or herself taking all the risks that it may bring. The second and the main idea of this work is to develop our tourist service. You will be able to read the description of our tourist service which in simple words is a service in which we offer to take groups of people to the Encanto river, that is located in a city of Cuscatlán ``Tenancingo" in El Salvador, in order to provide them with three main options which are: fishing, picnic and going hiking around the river. The third main idea of this work is to apply some strategies to be successful in entrepreneurship. We apply strategies such as: making alliances with other businessmen who are in the same area of tourism so as to earn more about the business and to get some support like, equipment and labor. So, the main parts of this work are to know about what is known as an entrepreneur, the description of how we will develop our tourist service and the strategies that will make our entrepreneurship a success.